2009
DOI: 10.1042/bio03104020
|View full text |Cite
|
Sign up to set email alerts
|

Under the lash: Demodex mites in human diseases

Abstract: Demodex mites, class Arachnida and subclass Acarina, are elongated mites with clear cephalothorax and abdomens, the former with four pairs of legs. There are more than 100 species of Demodex mites, many of which are obligatory commensals of the pilosebaceous unit of mammals including cats, dogs, sheep, cattle, pigs, goats, deer, bats, hamsters, rats and mice. Among them, Demodex canis, which is found ubiquitously in dogs, is the most documented and investigated. In excessive numbers D. canis causes the inflamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
86
0
9

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(110 citation statements)
references
References 10 publications
2
86
0
9
Order By: Relevance
“…Demodex mites are the most common parasite in humans, with a life-cycle lasting about 14-18 days [14]. There are many species of Demodex, but only D. folliculorum and D. brevis are found in the human body [3]. Demodex folliculorum inhabits the hair follicles of eyelashes while D. brevis lives deep in the meibomian glands and the sebaceous glands of the lash [5].…”
Section: Discussionmentioning
confidence: 99%
“…Demodex mites are the most common parasite in humans, with a life-cycle lasting about 14-18 days [14]. There are many species of Demodex, but only D. folliculorum and D. brevis are found in the human body [3]. Demodex folliculorum inhabits the hair follicles of eyelashes while D. brevis lives deep in the meibomian glands and the sebaceous glands of the lash [5].…”
Section: Discussionmentioning
confidence: 99%
“…Lacey et al 29 reported that the eye surface is protected by a bony protrusion, which is why the eyelid is not cleaned by cleansing the face. Westerners have sunken eyes, while Asians have protruding eyes.…”
Section: Discussionmentioning
confidence: 99%
“…Demodicosis is a common disease in canine practice caused by a proliferation of Demodex mites. These mites are normal commensal organisms in the hair follicles of many mammals . In the dog they are transmitted during the first days of life from the dam to the puppies .…”
Section: Pathogenesismentioning
confidence: 99%